36-(3x+4)=2(x+4)+x

Simple and best practice solution for 36-(3x+4)=2(x+4)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36-(3x+4)=2(x+4)+x equation:


Simplifying
36 + -1(3x + 4) = 2(x + 4) + x

Reorder the terms:
36 + -1(4 + 3x) = 2(x + 4) + x
36 + (4 * -1 + 3x * -1) = 2(x + 4) + x
36 + (-4 + -3x) = 2(x + 4) + x

Combine like terms: 36 + -4 = 32
32 + -3x = 2(x + 4) + x

Reorder the terms:
32 + -3x = 2(4 + x) + x
32 + -3x = (4 * 2 + x * 2) + x
32 + -3x = (8 + 2x) + x

Combine like terms: 2x + x = 3x
32 + -3x = 8 + 3x

Solving
32 + -3x = 8 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
32 + -3x + -3x = 8 + 3x + -3x

Combine like terms: -3x + -3x = -6x
32 + -6x = 8 + 3x + -3x

Combine like terms: 3x + -3x = 0
32 + -6x = 8 + 0
32 + -6x = 8

Add '-32' to each side of the equation.
32 + -32 + -6x = 8 + -32

Combine like terms: 32 + -32 = 0
0 + -6x = 8 + -32
-6x = 8 + -32

Combine like terms: 8 + -32 = -24
-6x = -24

Divide each side by '-6'.
x = 4

Simplifying
x = 4

See similar equations:

| x-5x+4x-7x= | | x^3-5x^2+2x=-1 | | 3+2k=17 | | x=7ln(y^2-48) | | 2w^2+7w=0 | | 7x=19(2x-7) | | -2x-x+1=0 | | 0.2x^5-2x^3+1.8x+5=0 | | 7+12p=-5 | | -2x-6=2-4-(x-1) | | 0.2x^5-2x^3+1.8x+2=0 | | R^2+10r-30=0 | | 3a+23=53 | | 4x^3+22x^2+24x=0 | | 2x^2-sinx+1=0 | | 16x^2-54x-16=0 | | 1-6x-3x=-17 | | (15)(13)+(15)(7)= | | 2a-18=34 | | 2x-sinx+1=0 | | 8n+2+5n=19 | | 4y+10=x | | 2x=-2-y | | 13=x(4-x) | | 45+0.25m=70+0.15m | | 2f+18=14 | | 2x+y-2z=14 | | V-4v+9=b-12 | | 3z+(-2)=8 | | 35-8r=-r+3(-3+5r) | | 5(2-x)-3(4-2x)=12 | | 0=-0.08t^2+4.48 |

Equations solver categories